The fruity coffee coffee & snacks - Abdul Rahim, Nur Syakirin; Ahmad, Nurhaida; Mohamad Noor, Nuraileen; Ahmad Suhaimi, Nurzairina; Muhammad Afzanizam, Nur Aina Shahira (2020)
The Fruity Coffee Café serves the best quality of coffee in every cup to share the specialities or privileges of our coffee with all the coffee lover. We also serve Choicy Nachos as our side dish to give selection for the customers if they would like to having meals in our café. Our coffee is made with full of uniqueness that will influence the customers to try it out. Our products give opportunities to taste the extraordinary of premium brewed coffee with the freshness of grape flavour. Our main menus are a premium brewed coffee of grape latte with the side dish of Choicy Nachos. A homemade Choicy Nachos is serving with special cheese sauce and it was made from tortilla wraps. Customers can choose the level of spiciness to satisfy their wants and fulfilled their cravings. These ideas to create a different taste of coffee latte are coming to overcome the dullness of the same coffee latte tastes and attract them to try the new flavour like ours. The Fruity Coffee Café are located near to the Mega View Hotel and in front of river view of Sungai Kuantan. We are choosing that place because it is a strategic location where customer can easily to get reach with us. As example, guests from nearest hotel enable to having their coffee and easy for the workaholics to make an online order if they won’t go out during lunch. Customers will get their favourite coffee and nachos at affordable price. It is because we are aim to achieve the regular customers for our coffee. The pricing tactics that we offered can help in attract the customer and maximise the profits. Our coffee and meals also can be bought from our physical café and by online order since we are provided a delivery to home or any current place. Most importantly, they will grab their coffee in everywhere at affordable price to satisfy their wants.